Analisis Makna Tari Maena dalam Pesta Adat Falőwa (Pernikahan) pada Masyarakat di Kecamatan Hiliduho Kabupaten Nias - Agus Tri Darman Laoli; Maringan Sinambela; Roida Lumbantobing; Elvri Teresia Simbolon; Sudirman Lase (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to Analysis of the Meaning of the Maena Dance in the Falőwa Traditional Feast (Wedding) in the Community in Hiliduho District, Nias Regency” Clifford Geertz's symbolism theory. The Maena dance is a traditional dance that is still preserved and has social, cultural, and spiritual values. This study uses a qualitative approach with descriptive methods. Data were obtained through observation, in-depth interviews with traditional leaders, Sanutunő Maena, and the community, as well as documentation. The results of the study indicate that the Maena dance has a social meaning that is reflected in the togetherness and brotherhood that are established among residents in its implementation. Solidarity is realized through collective participation, mutual assistance, and community cooperation in preparing and ensuring the success of the Falőwa (wedding) procession. The cultural meaning is seen in the preservation of elements of Nias tradition that have been passed down from generation to generation, while the spiritual meaning is seen in the expressions of gratitude, prayers, and blessings conveyed to the bride and groom. From Clifford Geertz's symbolism perspective, the movements, lyrics, dancer formations, and festive atmosphere of the Maena dance are cultural symbols conveying messages of togetherness, respect for tradition and ancestors, and hopes for a harmonious household life. Despite adaptations to changing times, the Maena dance in Hiliduho District maintains its traditional essence and values. In conclusion, the Maena dance serves not only as entertainment but also as a medium for transmitting values, strengthening social relationships, and symbolizing the cultural identity of the Nias people.